Domestikasi Barbodes Sellifer Dari Habitat Alami Menuju Budidaya Terkontrol - Kurniawan, Aan; Fahruzi, Muhammad Zahri; Sintiya, Sintiya; Febriani, Reva; Atmaja, Bekti Tri; Kurniawan, Ardiansyah (Jurnal Perikanan dan Kelautan, 2025)
The domestication of Striped Barb (Barbodes sellifer) was conducted at the Bangka Belitung University Hatchery from October  to December, 2025, to determine the fish’s adaptability from their natural habitat to a controlled cultivation environment. The domestication process included catching fish from peat swamp waters, acclimatization, rearing, feeding pellets, and monitoring water quality, growth, and survival. The results showed that the fish were able to adapt gradually, marked by an increase in average weight from 4.83 g to 5.47 g per fish, a specific growth rate of around 1%, and improved acceptance of artificial feed. Water quality parameters remained within the optimal range, namely temperature 27°C, pH 7.21, and DO 8.3 mg/L. The survival rate of 54.83% is considered reasonable for wild fish first reared in a controlled environment. This research provides a scientific basis for the development of sustainable groundfish cultivation in hatcheries and supports the conservation of local species.